2013
DOI: 10.1108/ec-05-2012-0103
|View full text |Cite
|
Sign up to set email alerts
|

Structural behaviour of concrete columns under natural fires

Abstract: Structured abstract.Purpose -The paper aims to give an insight into the behavior of reinforced concrete columns during and after the cooling phase of a fire. The study is based on numerical simulations as these tools are frequently used in structural engineering. As the reliability of numerical analysis largely depends on the validity of the constitutive models, the development of a concrete model suitable for natural fire analysis is addressed in the study. Design/methodology/approach -The paper proposes theo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 16 publications
1
22
0
Order By: Relevance
“…Also, the DHP appears to be approximately a linear function of R. Finally, considering a required Fire Resistance for the three columns, the tendency to exhibit failure during the cooling phase will be more pronounced for case 3 column than for the others and for case 1 column than for case 2. This confirms that delayed failures are more prone to arise in columns with low slenderness and massive sections, as mentioned in [10].…”
Section: Reinforced Concrete Columnssupporting
confidence: 86%
See 2 more Smart Citations
“…Also, the DHP appears to be approximately a linear function of R. Finally, considering a required Fire Resistance for the three columns, the tendency to exhibit failure during the cooling phase will be more pronounced for case 3 column than for the others and for case 1 column than for case 2. This confirms that delayed failures are more prone to arise in columns with low slenderness and massive sections, as mentioned in [10].…”
Section: Reinforced Concrete Columnssupporting
confidence: 86%
“…In a previous research [10], it was shown that for concrete columns the situations of delayed failure were more likely to arise for short-duration fires and columns with low slenderness or massive sections. It is shown here how these results can be interpreted in terms of the new indicator.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The mixes were produced by varying cement content, w/c ratio and type of admixture. The same type of Portland cement (CEM I 42.5 R conforming to EN 197-1:2011) and to the delayed temperature increase in the section core, and due to an additional loss of strength after cooling [6].…”
Section: Designmentioning
confidence: 99%
“…However, these studies have not answered the question about the influence of the additional reduction on the possible delayed failures of concrete members, which may occur long after the fire has been extinguished. The importance of exploring concrete behaviour after reaching the maximum temperatures has already been illustrated in recent scientific research [6], [7], where a new performance parameter was proposed to take into account the cooling phase in the assessment of fire resistance. The new parameter pointed to a large difference in the fire resistance of concrete members if the cooling phase of the fire curve is included in the analysis.…”
Section: Introductionmentioning
confidence: 99%